P1-S6.22 Characteristics of chlamydia testing by a large commercial laboratory corporation, USA, 2008–2010. (10th July 2011) - Kent, C; Tao, G; Hoover, K; Body, B; Nye, M
Abstract : Background: US guidelines recommend chlamydia screening for all sexually active young women, HIV-infected persons, and men who have sex with men (MSM). Several types of chlamydia tests are available, including nucleic amplification tests (NAATs), DNA probe, and culture. Different assays have different sensitivity and specificity, and sensitivity and specificity also varies by specimen type. Because reported chlamydia trends could be impacted by shifts in the proportion of tests and specimen types used by providers and laboratories, it is important to monitor changes in test usage to help interpret reported trends in morbidity. We examined chlamydia testing data from one of the two largest commercial laboratories in the USA Methods: Among chlamydia tests performed from June 2008—to July 2010 by this laboratory, we assessed the frequency of test types used by year, sex, specimen type, and positivity of these tests. Results: During these 2 years, 2.9 million specimens were tested for chlamydia. Among those tested, 86% were women. Tests performed were: 77% NAATs, 23% DNA probes, and 0.3% cultures. Between year 1 and 2, NAATs increased from 73% to 80% of all tests, and DNA probes decreased from 27% to 19%. Test type varied by sex; 88% of tests among men were NAATs compared to 75% among women. The top specimen types among women tested by NAAT were: 45% cervical, 35% urine and 18% vaginal. Chlamydia positivity varied by test type: 5.1% NAAT, 1.4% DNA probe, and 2.3% culture. Conclusions: NAATs were the most frequently used chlamydia test and their use increased over the evaluation period, creating a smaller market for other tests. Although vaginal swabs are the most sensitive specimen for testing women by NAAT, currently they are the least common specimen type used for testing. This may reflect the delayed introduction (FDA clearance) of the vaginal swab compared to other collection devices. Stocking the wide assortment of collection devices required for testing different specimens in different populations might also be a barrier for providers. Because these data are from one of the largest U.S. laboratories, with representation by insurance type and geography of the U.S. population, they can be useful for monitoring testing trends. Laboratory testing data also might be a valuable adjunct for national surveillance of chlamydia positivity trends that would not be dependent on provider or health department reporting nor small sample size from national surveys.